Integrative analysis of the metabolome and transcriptome provides insights into the mechanisms of flavonoid biosynthesis in Polygonatum - Xiaolin Wan; Qiang Xiao (PLoS ONE, 2025)
A noteworthy group of culinary and medicinal plants is Polygonatum species. They are known for their abundant flavonoid compound-rich rhizomes, which have antioxidative and anticancer activities. Using Polygonatum sibiricum Red (SXHZ) and Polygonatum kingianum var. grandifolium (HBES), we conducted transcriptome and metabolomic investigations to look into the molecular processes that control the manufacture of these flavonoids in Polygonatum plants. Seven distinct flavonoid metabolites were identified by the analytical data, with phloretin exhibiting a notable differential expression in the biosynthetic pathway. 30 genes with differential expression were found in both plants after further investigation, five of which are members of the transcription factor family associated with MBW. Thus, we suggest that Phloretin and the genes belonging to the MYB-related transcription factor family play a crucial role in controlling the flavonoid biosynthesis pathway in Polygonatum. This work lays the groundwork for a deeper comprehension of the biosynthesis and metabolic processes of flavonoids in Polygonatum, serving as an invaluable resource for the development of the polygonatum-related pharmaceutical industries as well as for the future breeding of Polygonatum plants with higher flavonoid content.